Gram-Negative Bacterial Infection in Thigh Abscess Can Migrate to Distant Burn Depending on Burn Depth - Victoria Hamrahi; Michael R. Hamblin; Walter Jung; John B. Benjamin; Kasie W. Paul; Alan J. Fischman; Ronald G. Tompkins; Edward A. Carter (Interdisciplinary Perspectives on Infectious Diseases)
Sepsis remains the major cause of death in patients with major burn injuries. In the present investigation we evaluated the interaction between burn injuries of varying severity and preexisting distant infection. We used Gram-negative bacteria (Pseudomonas aeruginosa and Proteus mirabilis) that were genetically engineered to be bioluminescent, which allowed for noninvasive, sequential optical imaging of the extent and severity of the infection. The bioluminescent bacteria migrated from subcutaneous abscesses in the leg to distant burn wounds on the back depending on the severity of the burn injury, and this migration led to increased mortality of the mice. Treatment with ciprofloxacin, injected either in the leg with the bacterial infection or into the burn eschar, prevented this colonization of the wound and decreased mortality. The present data suggest that burn wounds can readily become colonized by infections distant from the wound itself.